Direct anterior approach versus posterolateral approach for total hip arthroplasty in the treatment of femoral neck fractures in elderly patients: a meta-analysis and systematic review. (12th December 2023) - Jin, Zhiqiang; Wang, Lingge; Qin, Jun; Hu, Hao; Wei, Qingjun
Abstract: Objective: The purpose of this meta-analysis was to evaluate the postoperative clinical outcomes of elderly patients who underwent the direct anterior approach (DAA) versus those who received posterolateral approach (PLA) for total hip arthroplasty (THA) in the treatment of femoral neck fractures. Methods: An electronic search was conducted in databases including PubMed, Embase, Web of Science, the Cochrane Library, and CNKI from their inception to January 2022. We calculated the odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CIs) to assess the effect of DAA compared to PLA for the management of total hip arthroplasty (THA) in elderly patients using the dichotomous or continuous method with a random or fixed-effect model. Results: 15 studies involving 1284 patients were included; 640 patients receiving DAA and 644 patients receiving PLA. DAA had a longer surgery duration than PLA [WMD = 9.41, 95% CI (4.64, 14.19), I 2 =95.5%]; The amount of postoperative drainage [WMD= −3.88, 95% CI (−5.59, −2.17), I 2 =98.3%], length of incision [WMD= −3.88, 95% CI (−5.59, −2.17), I 2 =98.3%], blood loss [WMD= −3.88, 95% CI (−5.59, −2.17), I 2 =98.3%], hospitalization time [WMD= −3.88, 95% CI (−5.59, −2.17), I 2 =98.3%], and postoperative bedtime [WMD = −5.56, 95% CI (−7.11, −4.01), I 2 =99.0%], were similar between the two groups ( p  < 0.05). The HHS at 1 month, 12 months postoperatively [WMD = 7.58, 95%CI (5.70, 9.46), I 2 =89.5%; WMD= 2.56, 95%CI 0.11, 5.00, I 2 =93.2%] and the incidence of LFCN in patients were higher in the DAA group (OR = 2.91, 95% CI 1.26 to 6.71, I 2 =0.0%), while fewer patients in the DAA group suffered from postoperative dislocation than in the PLA group (OR = 0.26, 95% CI 0.11 to 0.60, I 2 =0.0%). No significant difference was observed in HHS at 1 week, 3 months, and 6 months postoperatively, VAS postoperatively at each time point, acetabular anteversion angle, acetabular abduction angle, wound infection, deep vein thrombosis, and intraoperative fracture ( p  > 0.05). Conclusions: DAA offers a quicker functional recovery and is less invasive with an earlier return to daily activities in older THA patients than PLA. However, DAA was found to be associated with a high incidence of lateral femoral cutaneous nerve injury and a low incidence of postoperative dislocation. Key messages: The present study aims to evaluate the clinical outcomes in elderly patients receiving DAA versus PLA for THA in the treatment of femoral neck fractures by mate-analysis. DAA offers a quicker functional recovery and is less invasive with an earlier return to daily activities in older THA patients. No significant difference was observed between the colchicine and comparators in terms of the need for HHS at 1 week, 3 months, and 6 months postoperatively, VAS postoperatively, acetabular anteversion angle, acetabular abduction angle, and complications (wound infection, deep vein thrombosis, and intraoperative fracture).